2020
DOI: 10.1111/pace.13930
|View full text |Cite
|
Sign up to set email alerts
|

Progress in zero‐fluoroscopy implantation of cardiac electronic device

Abstract: Fluoroscopy is the imaging modality routinely used for cardiac device implantation. Due to the rising concern regarding the harmful effects of radiation exposure to both the patients and operation staffs, many efforts have been made to develop alternative techniques to achieve zero‐fluoroscopy implantation. In this review, we describe the different methods aimed at avoiding the application of fluoroscopy in recent years, and evaluate their feasibility and safety in cardiac electronic device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Unlike the ablation procedures, the implant procedure of CRM devices requires the permanent placement of pacemaker or defibrillator leads within one or more chambers at specific positions. It has already been shown that the two EAM systems are capable of interfacing with pacemaker or defibrillator leads to provide their position within the previously created virtual 3D cardiac image during the implant procedure [ 30 , 51 ]. The Carto system, however, requires a custom-made connector to provide a workaround to see the device lead tip [ 51 ].…”
Section: The Obsolescence Of Fluoroscopy—transition To Alternate Imag...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the ablation procedures, the implant procedure of CRM devices requires the permanent placement of pacemaker or defibrillator leads within one or more chambers at specific positions. It has already been shown that the two EAM systems are capable of interfacing with pacemaker or defibrillator leads to provide their position within the previously created virtual 3D cardiac image during the implant procedure [ 30 , 51 ]. The Carto system, however, requires a custom-made connector to provide a workaround to see the device lead tip [ 51 ].…”
Section: The Obsolescence Of Fluoroscopy—transition To Alternate Imag...mentioning
confidence: 99%
“…It has already been shown that the two EAM systems are capable of interfacing with pacemaker or defibrillator leads to provide their position within the previously created virtual 3D cardiac image during the implant procedure [ 30 , 51 ]. The Carto system, however, requires a custom-made connector to provide a workaround to see the device lead tip [ 51 ]. ICE probes can already image a lead body, but in most platforms, the lead body is seen in a 2D cross-sectional slice.…”
Section: The Obsolescence Of Fluoroscopy—transition To Alternate Imag...mentioning
confidence: 99%
“…To our knowledge, this is the first report of using 3D‐mapping/ICE image integration to confirm lead positioning, thus forgoing fluoroscopy altogether. Fluoroless pacemaker implantation has been described before, 3 including a case in which a 3D mapping system (NavX EnSite Precision) to delineate the anatomy and visualize the pacemaker leads to guide their implant 4 . With NavX, the use of a dedicated sensored mapping catheter is not necessary, as any electrode can be visualized and used to create 3D geometry as long as it is not covered by insulation.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the catheter tip sensor is precisely located using triangulation in space [ 14 ]. Recently, the use of these devices has been preliminarily proposed to drastically reduce radiation dose during pacemaker and defibrillator lead implantation procedure procedures [ 15 , 16 , 17 , 18 , 19 ]. However, these techniques rely on the use of such special catheters, which are specific for electrophysiology and ablation studies.…”
Section: Introductionmentioning
confidence: 99%